State of preservation of the Red Barracks of the Owcza Góra Fort - Szostak, Bartosz; Trochonowicz, Maciej (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2019)
This paper is devoted to the object of the Red Barracks of the Owcza Góra Fort, which is located in Kłodzko. The building was erected as an external fort of the Kłodzko Fortress enabling observation of the foregrounds and protecting the hill from which the main fortress could be fired. The study presents the condition of the object, which has been unused for several decades and is subjected to destruction and degradation processes. The paper presents the results of inventory works, technical and laboratory tests.